If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = -4n + 2n Combine like terms: -4n + 2n = -2n 8 = -2n Solving 8 = -2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2n' to each side of the equation. 8 + 2n = -2n + 2n Combine like terms: -2n + 2n = 0 8 + 2n = 0 Add '-8' to each side of the equation. 8 + -8 + 2n = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 2n = 0 + -8 2n = 0 + -8 Combine like terms: 0 + -8 = -8 2n = -8 Divide each side by '2'. n = -4 Simplifying n = -4
| 7y-14x=42 | | 6(3.5+7s)=17.5 | | 12.1+x-8.2=4.4 | | Y=4(10)+6 | | -3+4(x-1)=12x+4-8x | | 22.5-6d=3.5(4.5d+4) | | y=x^2+x+2 | | t+3.43=7.4 | | 4x-6(2-x)=2 | | y=2x^2+x-1 | | -9b+3.6+5.5=29.5 | | 64-7x=2x+15 | | 1/2(4x-12)=4x | | p-16=s | | -f(3f-7)=0 | | 9w-35=7(w-3) | | z-10=y | | -13.8=v/7-2.6 | | 126+9x=47+18x | | 1/2x=7/10x+2/5 | | (-8a+29)/47-7 | | 3y=75 | | 6(x+2)+36=-2x | | 1x=1.5x+0.5 | | 6y-6=15 | | f^2+3f-12=6 | | 6x-7/4+3x-5/7 | | 6x-7/4 | | 5n^2-3n-9=0 | | 3x^3y^-1z^-1/x^-4y^0z^0 | | ((x^2-6x)/(x^2-36))*((x+6)/(x^2)) | | 4r(r)-100=0 |